Corporate governance and financial performance: Empirical evidence from public listed construction companies in Malaysia - Noordin, Nazrul Hazizi; Kassim, Salina (Inderscience Publishers, 2017)
This study examines the relationship between corporate governance structures and financial performance, focusing on construction companies listed on Bursa Malaysia. We apply a multiple regression analysis on data collected from annual reports of the companies for the years of 2009 and 2012. The corporate governance variables considered are board size, board independence, role duality, number of board meetings, while the financial performance of the listed companies is measured based on Tobin's Q ratio. This study finds that there is a significant positive relationship between number of directors on the board and financial performance of listed construction companies.